Ответы и объяснения

Лучший Ответ!
  • keret
  • середнячок
2013-04-21T18:26:26+04:00

sin x*cos x-6sinx*cosx-6=0 

sin x*cos x-6sinx*cosx-6cos^2(x)-6sin^2(x)=0|:(cos^2(x)) не равное 0

tgx-6tgx-6-6tg^2(x)=0

6tg^2(x)+5tgx-6=0

Пусть tg=x, тогда

6t^2+5t-6=0

D=25-4*6*(-6)=25+144=169

t=(-5+13)/12           t=2/3           tgx=2/3          x=arctg2/3+Пn,n принадлежит Z

или                         или             или               или

t=(-5-13)/12            t=-3/2          tgx=-3/2        x=-arctg3/2+Пk,k принадлежит Z

 

S={arctg2/3+Пn;-arctg3/2+Пk|n,k принадлежит Z}